Myomodulation Using Botulinum Toxin in Septorhinoplasty for Crooked Noses: Introducing the Concept and Application of Nasal Muscle Imbalance Theory - Wong, Eugene Hung Chih; D'Souza, Alwyn (Facial Plastic Surgery, 2023)
The role of septorhinoplasty for adequate correction of deviated nose is well documented, but the rationales and patterns for recurrences after proper rhinoplasty remain unclear. There has also been little attention given to the influence of nasal musculatures on the stability of nasal structures after septorhinoplasty. The aim of this article is to propose our nasal muscle imbalance theory, which may explain the potential reason for redeviation of the noses in the initial period after septorhinoplasty. We postulate that in a chronically deviated nose, the nasal muscles on the convex side will be stretched and develop hypertrophy after prolonged period of increased contractile activity. On the contrary, the nasal muscles on the concave side will undergo atrophy due to reduced load requirement. In the initial period of recovery after a septorhinoplasty to bring the nose back to midline, this muscle imbalance is still uncorrected with unequal pulling forces on the nasal structure because the stronger nasal muscles on the previously convex side is still hypertrophied and exert stronger forces compared with the previously concave side, therefore increasing the risk of redeviation of the nose back to the preoperative side until muscle atrophy occurs in the convex side and a balanced nasal muscle pull is achieved. We believe that postseptorhinoplasty botulinum toxin injections can be used as an adjunct in rhinoplasty surgery to effectively block the pulling actions of the stronger or overacting nasal muscles by speeding up the atrophy process while allowing patient's nose to heal and stabilize in the desired position. However, further studies to objectively confirm this hypothesis is required, which include comparing topographic measurements, imaging and electromyography signals before and after injections in postseptorhinoplasty patients. The authors have already planned a multicenter study to further evaluate this theory.
Keywords: septorhinoplasty; botulinum toxin; deviated nose; nasal muscle imbalance